Proximal phalanx shaft fracture with entrapment in the transverse retinacular ligament: a case report - Higginbotham, Devan O.; Tsai, Andrew G. (International Journal of Research in Orthopaedics, 2020)
We report the interesting case of a 33 years old male who underwent operative intervention for a left oblique proximal phalanx shaft fracture of the third finger which penetrated the transverse retinacular ligament (TRL). This patient required operative intervention due to entrapment of the bony fragment in the TRL which acted as a noose with traction on the fractured segment. The fracture was irreducible through a closed maneuver. The use of a dorsal approach allowed visualization of the fracture site and implementation of screws for fixation was deemed adequate secondary to the patient’s bone quality. He was placed in a volar splint at the conclusion of the case to allow for immobilization and protection of the repair. At follow-up, the patient’s radiographic images appeared appropriate and was progressing as expected. We report lessons learned from this case and describe a previously unreported fracture pattern and a possible method of reduction and fixation through a surgical approach in this report.